ANALISIS KELEMBAGAAN KELOMPOKTANI SISTEM INTEGRASI SAPI DAN KELAPA SAWIT (SISKA) DI KABUPATEN PELALAWAN - Edwina, Susy; Maharani, Evy; Kusumawaty, Yeni; Yusri, Jumatri; Yusmini, Yusmini (Jurnal AGRISEP, 2020)
Optimizing the area of oil palm plantations can be approached through the Cow and Palm Oil Integration System (SISKA), to increase efficiency and productivity through the integration of the plantation sub-sector with the livestock sub-sector. This study aimed to analyze the role of farmer groups and the institutional aspects of these groups in supporting the SISKA program in Pelalawan District. The approach used in this study was the institutional theory of Syahyuti. The role of farmer groups (as learning classes, production units and vehicles for collaboration) and institutional aspects of farmer groups (aspects of values, norms and behavior) were analyzed using Likert scale. The relationship between the roles and institutional aspects of the farmer groups was analyzed by Spearman Correlation test. The overall role of the farmer group is in the good category with a score of 3.49, most of the members (69.60%) answered in the fairly good and good category. The overall institutional aspects based on values, norms and behavior in the SISKA farmer group are in the good category with a score of 4.05. Correlation on sub-variable values, norms and behavior towards the role of farmers as units of production is a strong direct correlation. This shows that values, norms and behavior in groups affect, encourage and enhance the role of groups as learning classes that support the level of knowledge of farmers and the role of farmer groups as production unit.